(untitled) (Journal of Parents and Teachers, 2012)
In this article, the film proposed is Tangled. This film will help the students to learn the value of friendship. The film is based on the fairy tale of Rapunzel. If students do all the activities that are written down in this number will learn many different values and with the help of the teacher they will learn to apply those values in their daily live.